Aquilaria spp. (agarwood) as source of health beneficial compounds: A review of traditional use, phytochemistry and pharmacology - Hashim, Yumi Zuhanis Has-Yun; Kerr, Philip G.; Abbas, Phirdaous; Mohd Salleh, Hamzah (2016)
Ethnopharmacological relevance: Aquilaria spp. (agarwood) has been a part of Ayurvedic and Traditional Chinese Medicine for centuries. Agarwood has also been used as a traditional medicine in Southeast Asian countries, Bangladesh and Tibet. Its common uses include the treatment of joint pain, in- flammatory-related ailments, and diarrhoea, as well as a stimulant, sedative and cardioprotective agent. In this paper, we aim to provide an overview of the phytochemistry, ethnomedicinal use, pharmacological activities and safety of plant materials from Aquilaria spp. as an evidence base to further appraise its potential use as a source of health beneficial compounds. Materials and methods: Literature abstracts and full text articles from journals, books, reports and electronic searches (Google Scholar, Elsevier, PubMed, Read Cube, Scopus, Springer, and Web of Science), as well as from other relevant websites, are surveyed, analysed and included in this review. Results: A literature survey of agarwood plant materials showed that they contain sesquiterpenes, 2(-2- phenylethyl)-4H-chromen-4-one derivatives, genkwanins, mangiferins, iriflophenones, cucurbitacins, terpenoids and phenolic acids. The crude extracts and some of the isolated compounds exhibit antiallergic, anti-inflammatory, anti-diabetic, anti-cancer, anti-oxidant, anti-ischemic, anti-microbial, hepatoprotective, laxative, and mosquitocidal properties and effects on the central nervous system. Agarwood plant materials are considered to be safe based on the doses tested. However, the toxicity and safety of the materials, including the smoke from agarwood incense burning, should be further investigated. Future research should be directed towards the bio-guided isolation of bioactive compounds with proper chemical characterisation and investigations of the underlying mechanisms towards drug discovery. Conclusions: The traditional medicinal use of agarwood plant materials has provided clues to their pharmacological properties. Indeed, agarwood contains a plethora of bioactive compounds that now elegantly support their use in traditional medicine. As wild agarwood trees are critically endangered and vulnerable, sustainable agricultural and forestry practices are necessary for the further development and utilization of agarwood as a source of health beneficial compounds.